Synergy of Innovation between Hybrid Corn Seed Production and Seed Companies: A Review - Bahtiar Bahtiar; Darmawan Salman; Muhammad Arsyad; Muhammad Azrai (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The availability of seeds is one of the most essential aspects of agricultural development in developing countries and Indonesia is no exception. This requires adequate technological innovation and institutional support. This study aims to describe the synergy of innovation at the level of national companies that provide hybrid corn seeds to farmers. Three levels of company performance were compared namely well-established companies, middling, and less-developed companies. The results showed the performance of hybrid corn seed companies from 2019 to mid-2022 was mainly influenced by the degree of synergy between seed companies and their supporting institutions in implementing improvements in seed production technology. Established companies have better synergy with supporting institutions, hence, they can adequately apply seed production technology producing 4,900 tons of quality seeds, and distributing them to various regions specifically 12 provinces. Meanwhiles, companies that have low synergies with their supporting institutions are very weak, producing seeds only in small quantities at 400 tons. This implies that technological innovations and institution synergy for hybrid corn seed production can be applied by national companies with adequate support from local institutions.